Search for doubly charged higgs boson pair production in the decay to mu(+)mu(+)mu(-)mu(-) in pp collisions at sqrt[s]=1.96 TeV. - Abazov, V; Abbott, B; Abolins, M; Acharya, B; Adams, D; Adams, M; Adams, T; Agelou, M; Agram, J; Ahmed, SN; Ahn, S; Alexeev, G; et al. (2004)
A search for pair production of doubly charged Higgs bosons in the process pp -->H(++)H(--) -->mu(+)mu(+)mu(-)mu(-) is performed with the D0 run II detector at the Fermilab Tevatron. The analysis is based on a sample of inclusive dimuon data collected at an energy of sqrt[s]=1.96 TeV, corresponding to an integrated luminosity of 113 pb(-1). In the absence of a signal, 95% confidence level mass limits of M(H(+/-+/-)(L))>118.4 GeV/c(2) and M(H(+/-+/-)(R))>98.2 GeV/c(2) are set for left-handed and right-handed doubly charged Higgs bosons, respectively, assuming 100% branching into muon pairs.